Wind-tunnel studies of winds in Candlestick Park - Garrison, James A., author; Cermak, J. E. (Jack E.), author; Fluid Mechanics Program, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1970)
The purpose of this investigation is to determine if any low-cost, light-weight modification can be made either to the existing structure of Candlestick Park or to the proposed addition to improve the disturbing wind conditions now experienced in the stadium. The proposed addition will extend the upper spectator stands to completely enclose the playing field. A previous wind-tunnel study of winds in Candlestick Park found that the modeling technique yields wind patterns which correlate well with prototype patterns measured in a field study. The study conducted in 1963 also revealed that a combination of modifications to Bay View Hill and a partial dome over the stadium or a 60 ft high screen around the upper stands would be effective in elimination of objectionable features of the wind flow within the stadium. It proved impractical to make these modifications at that time. Since 1963, the southeast end of Bay View Hill has been modified further by excavations in a manner which the model study showed would improve the wind conditions. Therefore, the present study was undertaken with the hope that improvement of wind conditions might possibly be achieved through small changes in the existing or new portions of the stadium structure. This investigation has confirmed findings of-the previous study that simply extending the upper stands around the entire playing field will result in only a small improvement -and that the modifications to Bay View Hill have not been extensive enough to be of significant consequence. As found previously, it was observed that a SO to 100 ft screen around much of the upper stands and extending above the roof has a beneficial effect. None of the minor modifications investigated appeared to offer any significant level of wind control.
CER70-71JAG-JEC5.
May 1970.
Prepared for City of San Francisco Department of Public Works.
Keywords: Wind tunnel models; Buildings -- Aerodynamics; Stadiums -- California -- San Francisco -- Aerodynamics